A COMPARATIVE STUDY OF JUDICIAL RESTRAINT AND ACTIVISM ON THE MATERIAL REVIEW OF PRESIDENTIAL THRESHOLD IN THE CONSTITUTIONAL COURT - NAHDLIYAH, HADZIQOTUN; SASTRADINATA, DHEVINAYASARI; WINARNO, JATMIKO; TJAHJANI, JOEJOEN; YANTO, M. (Jurnal Independent, 2023)
AbstractThe doctrine of Judicial Restraint and Judicial Activism has become a debate indemocraticcountriesondecisionsrelatedtothepresidentialnominationthreshold(presidential threshold) made by the Constitutional Court. In the application of judicialrestraint, judges are more self-limiting in deciding a case and are more restrained in theirauthority, in contrast to judicial activism which is more active and brave in providing newlegal breakthroughs on the norms being tested. In this paper, the formulation of the problemto be discussed is How the Decision of the Constitutional Court Judges Applying the Doctrineof Judicial Restraint Against the Presidential Threshold Lawsuit in the Presidential Electionand the Development of Democracy in Indonesia and How the Relationship between theDecision of the Constitutional Court Judges Using the Doctrine of Judicial Activism Againstthe Presidential Threshold Lawsuit in the Presidential Election and the Development ofDemocracy in Indonesia. This paper also uses normative legal research methods, which is aprocess to analyze legal rules, legal principles and legal doctrines. The problem approach inthis writing is the statute approach and conceptual approach.